PENGARUH UKURAN PERUSAHAAN TERHADAP KETEPAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN DENGAN REPUTASI KAP SEBAGAI VARIABEL MODERATING - Teguh Erawati; Marthen Khondo (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
The purpose of this study is to examine the effect of firm size on timeliness of financial statement submission.This research is based on 63 manufacturing companies listed on the IDX in 2016-2019 that have passed the criteria, with a total sample of 252. However, because the Hosmer Lemeshow Test value is less than 0.005, the healing method is carried out through the highest error elimination. So as to produce a sample of 246 people who have data for research purposes. The method of sampling is purposive sampling and uses the Logistic Regression and Moderated Regression Analysis (MRA) technique.The results of this study indicate that Company Size (SIZE) have a significant positive effect on Timeliness of Financial Report Submission, while KAP's Reputation does not strengthen the relationship between Company Size on Timeliness of Financial Report Submission